The Emergence, Variation, and Evolution of Corporate Social Responsibility in the Public Sphere, 1980–2004: The Exposure of Firms to Public Debate - Lee, Sun Young; Carroll, Craig E. (2011)
This study examined the emergence of corporate social responsibility (CSR) as a public issue over 25 years using a content analysis of two national news- papers and seven regional, geographically-dispersed newspapers in the U.S. The present study adopted a comprehensive definition encompassing all four CSR dimensions: economic, ethical, legal, and philanthropic. This study examined newspaper editorials, letters to the editor, op-ed columns, news analyses, and guest columns for three aspects: media attention, media prominence, and media valence. Results showed an increase in the number of opinion pieces covering CSR issues over the 25-year period. The prominence of each of the four CSR dimensions varied over time. Each of the four CSR dimensions had its moment of media prominence when it was more important than the other dimensions. The most prevalent valence of the opinion pieces was negative; the volume of negative pieces increased over the 25 years, whereas the number of opinions with positive, neutral, and mixed tones showed little change over time. The study concludes by tracing the implications of the role of the news media for business ethics research.
Keywords: Public Opinion; Newspaper; Media valence; Media prominence; Media Attention; Media; LETTERS to the editor; Editorials; Corporate Social Responsibility; Columns